2018
DOI: 10.3389/fphar.2018.00123
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Ameliorate Thiram-Induced Tibial Dyschondroplasia via Regulation of WNT4 and VEGF Expression in Broiler Chickens

Abstract: Tibial dyschondroplasia (TD) is main bone problem in fast growing poultry birds that effect proximal growth plate (GP) of tibia bone. TD is broadly defined as non-vascularized and non-mineralized, and enlarged GP with tibia bone deformation and lameness. Icariin (Epimedium sagittatum) is a traditional Chinese medicine, which is commonly practiced in the treatment of various bone diseases. Recently, many researcher reports about the beneficial effects of icariin in relation to various types of bone conditions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 50 publications
4
21
0
Order By: Relevance
“…While extreme hypertrophy of chondrocytes increase in the number of immature chondrocytes, degeneration and necrosis of chondrocytes were observed in the tibiotarsal joint. This was accompanied by a vascularization (Rath et al, 2007 ve 5;Imık et al, 2012;Nabi et al, 2016b;Zhang et al, 2018). The histopathological findings observed in the broiler chickens with TD lesions in the present study were determined to be compatible with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While extreme hypertrophy of chondrocytes increase in the number of immature chondrocytes, degeneration and necrosis of chondrocytes were observed in the tibiotarsal joint. This was accompanied by a vascularization (Rath et al, 2007 ve 5;Imık et al, 2012;Nabi et al, 2016b;Zhang et al, 2018). The histopathological findings observed in the broiler chickens with TD lesions in the present study were determined to be compatible with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…For this reason, the studies investigating the factors that are likely to play a role in the pathogenesis of the disease are becoming prominent recently. In these studies, Hypoxia inducible factor-1 (HIF-1α), (Genin et al, 2008;Mehmood et al, 2017) vascular endothelial growth factor (VEGF) (Zhang et al, 2013;Zhang et al, 2018) and HSPs (Genin et al, 2012; release were shown by several genes (Tian et al, 2013(Tian et al, , 2014, biochemical and immunohistochemical methods in poultry with TD lesions (Genin et al, 2012;Rath et al, 2005;Nabi et al, 2016a,b;Shahzad et al, , 2015Iqbal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The control group was fed the full-price diet and free drinking water daily, and other groups were fed the full-fledged diet on the 3rd to the 7th day with 50 mg/kg Thiram. Furthermore, we used formulated diet according to Zhang et al (2018c) , which was also tested to eliminate the effect and influence of phytoestrogens in the diets from the effects of TFRD. From the 8th day, total of 50 chickens in the TFRD group were orally fed with 20 mg/kg/day TFRD until the end of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it is reported that TD accounts for 30% of all bone disorders in poultry with approximately 10% morbidity rate in China leading to substantial reduction in the farmer's profit margin (Zhang et al, 2018). Clinical and subclinical effects of TD include; reduced immunity, osteomyelitis, compromised growth rate and breast cyst formation, that ultimately reduce carcass and meat quality besides raising ethical and welfare issues (Tian et al 2013;Shahzad et al, 2014a;.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and subclinical effects of TD include; reduced immunity, osteomyelitis, compromised growth rate and breast cyst formation, that ultimately reduce carcass and meat quality besides raising ethical and welfare issues (Tian et al 2013;Shahzad et al, 2014a;. Thiram induces TD in chicks, affects liver health (Iqbal et al, 2016), checks the angiogenesis and disrupts the normal arrangement of chondrocytes (Zhang et al, 2018). These problems are well documented formerly but fundamental etiology is still not clear (Iqbal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%